Cross linking to tissue transglutaminase and collagen favours gliadin toxicity in coeliac disease. Issue 4 (27th September 2005) - Dieterich, W; Esslinger, B; Trapp, D; Hahn, E; Huff, T; Seilmeier, W; Wieser, H; Schuppan, D
Abstract : Background and aims: Intestinal inflammation in coeliac disease is driven by the gluten fraction of wheat proteins. Deamidation or cross linking of gluten peptides by tissue transglutaminase (tTG), the coeliac disease autoantigen, creates potent T cell stimulatory peptides. Therefore, our aim was to identify the reaction patterns of gluten peptides, intestinal extracellular matrix proteins, and tTG. Methods: tTG activity was analysed by incorporation of monodansyl cadaverine into gliadins. Fluorescence labelled tTG reactive short gliadin peptides were used to demonstrate their deamidation and explore their cross linking patterns with tTG itself or extracellular matrix proteins. Patient sera and controls were checked for autoantibodies to matrix proteins. Results: Gliadins α1–α11, γ1–γ6, ω1–ω3, and ω5 were substrates for tTG. tTG catalysed the cross linking of gliadin peptides with interstitial collagen types I, III, and VI. Coeliac patients showed increased antibody titres against the collagens I, III, V, and VI. Conclusions: tTG formed high molecular weight complexes with all tested gliadins. As all tested gliadins were substrates for tTG, the tTG catalysed modifications were not restricted to single gliadin types and epitopes. Furthermore, haptenisation and long term immobilisation of gliadin peptides by tTG catalysed binding to abundant extracellular matrix proteins could be instrumental in the perpetuation of intestinal inflammation and some associated autoimmune diseases in coeliac disease.